17β-Estradiol transcriptionally modulates Nlrp1 and Nlrp3 inflammasomes in gonadectomized rats with inflammation. (August 2015) - Gómez López, Modesto; Domínguez López, Aarón; Abarca Rojano, Edgar; Rojas Hernández, Saúl; Martínez Godínez, María de los A.; Miliar García, Angel; Campos Rodríguez, Rafael
Abstract Context: It has been reported that 17β-estradiol (E2) reduces the expression of inflammatory molecules, but there are no data that show the effect of E2 on the transcriptional regulation of innate immunity-related molecules and inflammasomes. Objective: To study the effect of 17β-estradiol (E2) on the transcriptional expression of the NLR family, pyrin domain containing 1 (Nlrp1) and (Nlrp3) inflammasomes, which are mediators of inflammation. Materials and methods: Inflammation was induced in adult female gonadectomized (Gdx) rats by intramuscular injection of complete Freund's adjuvant (CFA). Measurements were taken at different times after the treatment. Gene expression determinations were done by quantitative real-time polymerase chain reaction (qRT-PCR). Results: CFA-induced inflammation increased the transcription of Nlrp3, IL-1β (p < 0.05), vascular cell adhesion molecule 1 (VCAM1), E-selectin and estrogen receptor 1 alpha (ERα) (p < 0.001) and decreased the transcription of Nlrp1, Caspase-1, IL-33, NFKB1, ICAM1, ICAM2, GCRα, GCRβ, UCP3 and PGC1α (p < 0.001) compared to the control. The administration of E2 to the inflamed tissue significantly increased the expression of Nlrp1, NFKB1, ERα, UCP3, Caspase-1, E-selectin (p < 0.001), IL-18 and ERα (p < 0.05) and decreased IL-1β and VCAM1 (p < 0.005) compared to the control. Discussion and conclusion: CFA differentially modulates the transcription of inflammasome-related genes and the administration of E2 increases the expression of ERα and Nlrp1 together with NFKB1, a key molecule in the activation of the inflammasomes. Finally, an analysis using the web interface GeneMANIA revealed an interaction between several genes, indicating a functional correlation in this model.